8.38. Oblicz wartość wyrażenia: a) (4sin alpha – 5cos a)/(cos a + 3sin a) jeśli tg * alpha = 5 (cos alpha + 2sin alpha)/(sin alpha – cos alpha), cos alpha * cos alpha =4 b) b) (sin alpha – cos alpha)/(cos alpha) 2/3 Bez wyznaczania wartości sinusa (2 – 2sin^2 alpha)/(sin^2 alpha) (8sin alpha – cos alpha)/(7sin alpha + 6cos alpha) (2sin^2 alpha – cos^2 alpha)/(2cos^2 a + sin^2 alpha), jesiict jeśli sictg * alpha = 3 ctg * alpha = 2 . kąta a, b) d)

8.38. Oblicz wartość wyrażenia: a) (4sin alpha – 5cos a)/(cos a + 3sin a) jeśli tg * alpha = 5 (cos alpha + 2sin alpha)/(sin alpha – cos alpha), cos alpha * cos alpha =4 b) b) (sin alpha – cos alpha)/(cos alpha) 2/3 Bez wyznaczania wartości sinusa (2 – 2sin^2 alpha)/(sin^2 alpha) (8sin alpha – cos alpha)/(7sin alpha + 6cos alpha) (2sin^2 alpha – cos^2 alpha)/(2cos^2 a + sin^2 alpha), jesiict jeśli sictg * alpha = 3 ctg * alpha = 2 . kąta a, b) d)